A Systematic Literature Review with Meta-analysis on Risk Factors for Hypertension - Oryza Filial Zulkarnain; Yura Witsqa Firmansyah; Muhammad Fadli Ramadhansyah; Ayu Widyawati; Ike Rachmawati; Muslyana Muslyana; Ramadani Sukaningtyas; Rafika Rafika; Afdal Hardiyanto; Hanung Nurany; Anshah Silmi Afifah; Aziz Yulianto Pratama (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Hypertension is a manifestation of hemodynamic imbalances resulting in various cardiovascular complications and others in the body systems. The prevalence of hypertension in Indonesian adults aged 18 years was 34.1%, and it increased by 8.3%. Globally, it accounts for about 60% of deaths. This study aimed to analyze risk factors for hypertension in industrial workers. Methods: This study used a meta-analysis, a statistical method that combines previous studies to find an effect size value or summary on JASP software. Data in this study came from database online and were sorted according to the inclusion-exclusion criteria following PRISMA. In the final step, 14 research articles were collected. Results and Discussion: Noise intensity had a 1.974 times greater risk on the prevalence of hypertension in industrial workers; work period had 2.316 times greater risk; duration of exposure gave a 1.716 times greater risk; and smoking had a 1.896 times greater risk. Conclusion: The highest risks for the incidence of hypertension in industrial workers come from period of work, noise intensity, and smoking habits; while, the lowest is in the length of exposure